Development of a colloidal gold-immunochromatography assay to detect immunoglobulin G antibodies to Treponema pallidum with TPN17 and TPN47 - Lin, Li-Rong; Fu, Zuo-Gen; Dan, Bing; Jing, Guang-Jun; Tong, Man-li; Chen, De-Teng; Yu, Yang; Zhang, Chang-Gong; Yang, Tian-Ci; Zhang, Zhong-Ying (Diagnostic microbiology and infectious disease, 2010)
Syphilis remains a worldwide public health problem; it is necessary to develop a new diagnostic approach that is easier and faster than conventional tests. Here, we report a new testing method named colloidal gold-immunochromatography assay (GICA) to detect syphilis instead of fluorescent treponemal antibody–absorption (FTA-Abs). Syphilis-specific immunoglobulin G (IgG) antibody was detected with GICA established on syphilis-specific recombinant proteins, TPN17 and TPN47. FTA-Abs Treponema pallidum (TP)-IgG was set as the gold standard. A GICA test was performed to detect the serum of 14 967 subjects who took a serologic test for syphilis at the Xiamen Center of Clinical Laboratory, Fujian, China, from March 2009 to February 2010, among which 1326 cases were diagnosed as syphilitic. The results showed that the sensitivity, specificity, and positive predictive value were 99.38% (1279/1287), 99.96% (12 975/12 980), and 99.61% (1279/1284), respectively. The positive rate between the 2 test methods had no significant difference ( χ 2 = 0.003, P > 0.05). Detection on 500 interference specimens indicated that the biologic false-positive rate of the GICA test was extremely low and free from other biologic and chemical factors. The characteristics of GICA TP-IgG correspond to that of FTA-Abs TP-IgG (EUROIMMUN Medizinische Labordiagnostika, Germany). The GICA test is convenient, fast, and inexpensive, and it can be used both as a confirmatory test and a screening indicator, instead of FTA-Abs TP-IgG.